Effects of Eplerenone on Blood Pressure and Echocardiographic and Serum Biochemical Variables in Five Healthy Dogs: A Pilot Study. (13th January 2020) - Arita, Shinji; Arita, Noboru; Hikasa, Yoshiaki
Abstract : Eplerenone (EP), an aldosterone antagonist, is reported to produce renal and cardiac protective effects in noncanine species. However, there are no detailed reports available on cardiovascular effects of EP in dogs. This study aimed to determine effect of EP on echocardiographic parameters, blood pressures, and biochemical variables in healthy dogs. Five healthy Beagle dogs were randomly divided and repeatedly used in each of 3 dose groups, receiving 2.5, 5, or 10 mg/kg BW EP orally q24 h for 4 wks. Serum biochemical test, blood pressure, and Doppler echocardiography measurements were performed before EP administration and at 1, 2, and 4 weeks after EP administration. Treatment with EP reduced mean blood pressure in a dose-dependent manner and significantly (but in a dose-independent manner) decreased left atrium/aorta ratio, early diastolic transmitral flow, early diastolic transmitral flow/late diastolic transmitral flow, peak velocity of early diastolic transmitral flow/peak velocity of early diastolic mitral annular motion, left ventricle and right ventricle Tei indices, stroke volume, cardiac output, and mid systole myocardial velocity gradient 1 to 4 weeks after administration. Deceleration time of early diastolic transmitral flow significantly increased after EP administration. No significant changes were observed in serum biochemical variables. The results indicated that EP might reduce preload, thereby decreasing left atrial size. In addition, reduction of left ventricular stiffness may have theoretically taken place but this could not be tested using the present study design. It is suggested that EP administration within the dose range used in this study is safe for administration to healthy dogs. Further studies are needed to explore both safety and efficacy, as well as to seek a recommended dose range of EP treatment in client-owned dogs with heart disease.